METODE PELAKSANAAN PEKERJAAN DAK SHELTER PINTU AIR BCPL. 158 PADA PROYEK RENTANG IRRIGATION MODERNIZATION PROJECT - Muharomah, Wulan Marliana; Toruan, Erni Sari Lumban (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Building a dam sluice certainly requires a long time and process. The process starts from the dewatering stage to the construction of the sluice gate building and then the maintenance stage. In the shelter or door house there are building components, one of which is the dak. The method of implementation of the work of making dak shelter sluice gate is in the form of preparatory work which includes the planning stage, cleaning work, measurement work, mobilization of tools and materials and scaffolding installation work, formwork work, drilling work, casting work, maintenance and finishing work in the form of formwork dismantling work. The materials used in the implementation of the sluice gate shelter dak work are concrete type K175 or f'c 14.5 Mpa, by using D13 and D16 fin reinforcement iron with each reinforcement distance of 200 mm. In the implementation of practical work, the maintenance of concrete after casting is carried out by direct watering which is carried out in 2 ways, namely direct watering with a water pump assisted by a hose / pipe and direct watering with a bucket.